Early Christianity in the Lycus Valley: Early Christianity in the Lycus Valley - Huttner, Ulrich (Ancient Judaism and Early Christianity Ser., 2013)
With Early Christianity in the Lycus Valley Ulrich Huttner offers a microstudy of Christian history in southwestern Asia Minor (first to fifth century C.E.).